Representasi Gambar Hijrah Milenial di Media Online: Analisis Wacana Kritis Multimodal dan Gender: The Representation of Millenial Hijrah Image in Online Media: Gender and Multimodal Critical Discourse Analysis - Gina Giftia Azmiana Delilah; Diena Rauda Ramdania; Busro Busro (Direktorat Jenderal Bimbingan Masyarakat Islam, 2021)
This study aims to see how millennial hijrah is represented in images and how men and women are represented in hijrah images. Feminist methodology is used with multimodal and gender as a tool of analysis. This is based on the assumption that a text in the study of critical discourse analysis is not to be value-free and has a specific ideological purpose. Data collection techniques by searching on google images with the keyword 'gambar hijrah'. The results showed that the majority of hijrah in the google image was represented by women. There are indications of the dominance of patriarchal ideology in millennial hijrah and gender inequality in women. In addition to patriarchal ideology, the struggle for the hegemony of signs and gender hegemony in the millennial hijrah cannot be separated from the textual reading of the al-Qur'an and al-Hadith.